Intracavitary Transmissible Venereal Tumor in a Bitch - Schmitz da Silva, Maria Eduarda; Bocca, Maysa; Silva Rodrigues, Natália; Lancia Pereira, Marcy; Tony Ramos, Adriano (Acta Scientiae Veterinariae, 2024)
Background: Transmissible venereal tumour (TVT), also called Sticker Tumour, is a round cell tumour whose transmission occurs mainly through sexual contact between animals or direct transplantation of the neoplastic cell through licking or through direct contact with the lesioned area. TVT is the most common tumor found in stray dogs and predominantly affects the genital area and, in case of bitches, occurs in the vagina and foreskin, as well as the oral and nasal cavities. Intracavitary TVT is rarely reported. The aim of this paper is to report a case of an old neutered bitch affected by vaginal and intracavitary TVT, treated at the Veterinary School Clinic (CVE) of the Federal University of Santa Catarina (UFSC), Curitibanos campus, Brazil. Case: An approximately 10-year-old mixed breed bitch, weighing 18,5 kg and, neutered 2 years previously at the same institution, was brought by her owner, who reported dyskinesia, constipation, and serosanguinous vaginal discharge for a few weeks. Physical examination showed a row of 4 smooth, round masses with a soft consistency ranging from 1 to 2 cm at the bottom of the vaginal roof. The patient was referred for an ultrasound (US) and a vaginal swab was taken for cytological examination, whose result demonstrated TVT. The result of the US scan showed a heterogeneously shaped structure, with a more hypoechogenic center in relation to the periphery and irregular contours, measuring around 2.63 x 6.10 cm, in the uterine topography caudally to the bladder. Exploratory laparotomy was performed with total removal of the mass, which was surrounding the proximal urethra, and the material was sent for histological and cytological analysis, whose both results indicated TVT. Chemotherapy was then initiated, with 6 intravenous administrations of vincristine (0.5 mg/m 2 ) with an interval of 15 days between each administration. The animal underwent a total of 6 chemotherapy sessions, without complete improvement of the vaginal tumours. A 2nd chemotherapy protocol based on doxorubicin was suggested, which was not accepted by the owner. Three months after the end of the original hemotherapy protocol, the patient was assessed again and it was found that there had been no progression of the vaginal masses on vaginal palpation and no signs of recurrence of the intracavitary mass on ultrasound. Discussion: TVT is a venereal tumor that affects almost 100% of non-neutered animals, males and females. In the case of bitches, the most common sites are the vagina (53%), vulva (13%) and extragenital areas (14%). This animal had no intracavitary mass at the time of her castration 2 years earlier. At the time of diagnosis, she had the extragenital form of the tumor, consisting of an intra-abdominal mass, in addition to the genital masses in the vaginal roof. The chemotherapy drug vincristine is the drug of choice for the treatment of transmissible venereal tumors, due to its high efficacy associated with 4 to 6 sessions. However, in this case, there was no total improvement, so it was classified as a case of proven pharmacological resistance as the chemotherapy was ineffective for the complete regression of the tumor. It was therefore concluded that the occurrence of intracavitary TVTs, although rare, warrants a thorough physical examination combined with diagnostic tools such as ultrasound and histology, even in castrated old patients. Keywords: TVT, neoplasm, round cells, vagina, Sticker tumor, dog. Título: Tumor Venéreo Transmissível intracavitário em uma cadela Descritores: TVT, neoplasma, células redondas, vagina, tumor de Sticker, canino.